An Analytic View of the Selected Methods of Performance Evaluation in Slovak Business Entities - Coculova, Jana (Advances in Social Sciences Research Journal, 2016)
Performance evaluation as one of the basic features of human resource management is an important tool for stimulating employees so they can achieve the pre-set goals and improve the performance of the whole business entity. The choice of the right performance evaluation method should take into account a number of criteria the fulfillment of which is a prerequisite for their acceptance by entity’s employees. The paper deals with the comparison of selected methods from the standpoint of its perception by evaluated employees. The paper also presents results of the research conducted in Slovak business entities. Moreover, the research’s aim was to determine statistically significant differences between selected performance evaluation methods in terms of perception of selected criteria like objectivity, validity, the incentive effect, the impact on remuneration and career progression. For this purpose the research tested 5 statistical hypothesis using Skillings-Macs test to test multiple measurements and the post-hoc test.